TANGGUNG JAWAB WALI TERHADAP ANAK YANG BERADA DI BAWAH PERWALIANNYA (SUATU PENELITIAN DI KOTA BANDA ACEH) - Zahratul Idami (Faculty of Law, Universitas Jenderal Soedirman, 2012)
The resut of the research shows that there were guardians who did not make the list of the children’s property and also did not record all the changes of property of the children under their guardianship when he started the position. There were also trustees who did not give all property of the children even thoug their already reached the age of 18 and already get married. It was caused by some factors such as their lack of knowledge on his duty and responsibility toward the children under their guardianship, their opinion that the children were not capable enough to manage the money by himself due to their bad attitude. Lack of socialization;more feeling of relationship; unclear of mechanism of guardianship;unavailableof controlling institution which is really consent to the guardianship. The efforts can be done: a continous controlling and deep toward the guardians and the children under their guardianship. Also it is better if the government make a strict regulation related to the guardianship. Keywords : responsibility, guardian, guardianship